Bipolar-CMOS-DMOS Process-Based a Robust and High-Accuracy Low Drop-Out Regulator - Luwei Pan; Li Zhou; Tao Sun (Universitas Ahmad Dahlan, 2014)
A 40V BCD process high-accuracy and robust Low Drop-Out Regulator was proposed and tape-out in CSMC; the LDO was integrated in a LED Control and Driver SOC of outdoor applications. The proposed LDO converted the 12V 40V input power to 5V for the low voltage circuits inside the SOC. The robustness of LDO was important because the application condition of the SOC was bad. It was simulated in all process corner, -55℃ 150℃ temperature and 12V 40V power voltage conditions. Simulation result shows that the LDO works robustly in conditions mentioned above. The default precision of LDO output voltage is ±2.75% max in all conditions, moreover, by utilizing a trim circuit in the feedback network, the precision can be improved to ±0.5% max after being trimmed by 3 bit digital trim signal Trim[3:1]. The total size of the proposed LDO is 135um*450um and the maximum current consumption is 284uA.